A triboelectric nanogenerator based on waste tea leaves and packaging bags for powering electronic office supplies and behavior monitoring. (June 2019) - Xia, Kequan; Zhu, Zhiyuan; Fu, Jiangming; Li, Yueming; Chi, Yue; Zhang, Hongze; Du, Chaolin; Xu, Zhiwei
Abstract: Triboelectric nanogenerators based on reusing waste aluminum plastic bags and biodegradable tea leaves (after drinking) will not only reduce the waste of resources but can also mitigate environmental pollution and reduce energy consumption. In this paper, we propose a novel tea-leaf triboelectric nanogenerator using aluminum plastic bags (TAP-TENG). The approximate values of open circuit voltage ( V oc ), short-circuit current ( I sc ), and output power density of the fabricated TAP-TENG could reach 792 V, 42.8 μA, and 488.88 μW/cm 2, respectively. The generated electrical output is capable of directly powering 179 green high-power light-emitting diodes (LEDs). Additionally, a honeycomb lantern TAP-TENG structure is proposed, which can be used not only to harvest mechanical energy, for example, turning books and pulling drawers, but can also detect various touching states, such as knocking, pressing, and stroking. Additionally, we propose a power management circuit to power various electronic office supplies, such as a digital temperature-humidity meter, electronic calculator and electronic watch. The tea leaves and aluminum plastic bags used for TENG construction are commercial and waste office commodities and the fabricated TENG are applied for powering and sensing purpose within the office. This study provides a simple and cost-effective method of fabricating an energy harvester to power environmental monitoring devices, which will promote the large-scale and intelligent practical application of TENGs. Graphical abstract: Image 1 Highlights: Biodegradable tea leaves (after drinking) and waste aluminum plastic bags are firstly introduced to make TENG, which can power 179 green LEDs. A honeycomb lantern TAP-TENG structure is proposed for harvesting mechanical energy. Simple step processes (tape pasting, etc.) and household materials (tea, waste bag, double sided tap, etc.) are developed for simple manufacturing.